Heterogenous bioluminescence patterns, cell viability, and biofilm formation of Photobacterium leiognathi strains exposed to ground microplastics - De Jesus, Rener; Iqbal, Sameera; Mundra, Sunil; AlKendi, Ruwaya (Frontiers in Toxicology, 2024)
Microplastics (MPs) have been detected in various aquatic environments and negatively affect organisms, including marine luminous bacteria. This study investigated the differences in bioluminescence patterns, cell viability, and biofilm formation of Photobacterium leiognathi strains (LB01 and LB09) when exposed to various concentrations of ground microplastics (GMPs; 0.25%, 0.50%, 1%, or 2% [w/v] per mL) at 22°C or 30°C for 3.1 days (75 h) and 7 days. The strains exhibited heterogenous responses, including variable bioluminescence patterns, cell viability, and biofilm formation, due to the GMPs having effects such as hormesis and bioluminescence quenching. Moreover, the bioluminescence and cell viability differed between the two strains, possibly involving distinct cellular mechanisms, suggesting that GMPs affect factors that influence quorum sensing. Furthermore, the biofilm formation of LB01 and LB09 was observed following exposure to GMPs. Both strains showed increased biofilm formation at higher GMP concentrations (1% and 2%) after 3.1 days at 30°C and 22°C. However, in the 7-day experiment, LB01 significantly (p < 0.05) increased biofilms at 22°C, while LB09 significantly (p < 0.05) produced biofilms at 30°C. These findings highlight the strain-specific responses of Phb. leiognathi to MP pollutants. Therefore, this study underscores the importance of evaluating MPs as environmental stressors on marine microorganisms and their role in the ecophysiological repercussions of plastic pollution in aquatic environments.